Deceleration characteristics of elite Australian male field hockey players during an Olympic tournament - Chesher, S. M.; Netto, K. J.; Appleby, B. B.; Jacques, A.; Wild, C. Y. (Journal of Science and Medicine in Sport, 2019)
Objectives: This study described the deceleration efforts of the Australian men`s field hockey team during the 2016 Olympics by categorising efforts into `bands` of intensity; and comparing the deceleration intensity and frequency by player position, game period and opponent. Design: Descriptive retrospective analysis. Methods: Global positioning system sensors (MinimaxX S4, Catapult Sports Pty. Ltd., Melbourne, Australia; 10 Hz) were worn by 15 male field hockey players during six games of the 2016 Olympic tournament. Results: There were 8998 individual deceleration efforts (=-3 ms-2) performed over the tournament with the most intense effort measured at -13.6 ms-2. Deceleration intensity `bands` were calculated using Receiver Operator Characteristic (ROC) curves as low intensity = -3 to -5.99 ms-2; medium intensity = -6 to -8.99 ms-2; high intensity = -9 to -11.99 ms-2; and, very high intensity = <-12 ms-2. There were no significantly different decelerations between field positions but decelerations performed within game period one were more intense than game period two (-0.11 ± 0.01 ms-2, p < 0.001). Deceleration efforts were more frequent in game period one than two [X2(3, N = 8997) = 12.00, p = 0.007]. Conclusions: Decelerations are common in elite field hockey and very high intensities are present. These findings, in conjunction with other metrics can be used as a tool to monitor the load associated with training and match play in field hockey.